Impact of reactive precursors on the sintering of tin monoxide. Issue 4 (April 2022) - Bhoi, Subhransu Subhasis; Duttine, Mathieu; Chung, U-Chan; Josse, Michaël; Suchomel, Matthew R.
Highlights: Tin monoxide can be densified (∼ 90 %) by low temperature Cool-SPS processing. Demonstrated for both conventional SnO and reactive tin(II) oxyhydroxide precursors. Starting precursor powder impacts processing conductions, final microstructure. Resulting ceramic transport properties controlled by microstructure. Abstract: The thermodynamic stability limits of Sn(II) under ambient conditions imposes constraints on the densification of divalent tin based oxides. In the case of tin monoxide (SnO), a low temperature (≤ 300 °C) electric field assisted processing route (Cool-SPS) affords densification up to 90 % of theoretical density. This is demonstrated for both conventional SnO and reactive tin(II) oxyhydroxide [Sn6 O4 (OH)4 ] precursor powders. The choice of starting precursor impacts both the optimized processing parameters and the resulting ceramic microstructure. Characterizations of phase content and stability have been performed on both the precursor powders and resulting ceramics. Preliminary electrochemical property measurements are presented and their connection to observed microstructures and choice of initial precursor is discussed.